Megafauna communities from abyssal sites along the Gloria Fracture Zone (NE Atlantic) - Ferreira, T. (2022)
Fracture zones are areas of poorly known abyssal landscapes and benthic faunal communities. During the R/V Meteor M162 cruise several imagery surveys were performed using a TV-CTD guided camera system along four main areas of the Gloria fault system, between the Terceira ridge and the Madeira Tore Rise. Based on these records, we were able to characterize - for the first time - the megafaunal composition, their abundance and diversity along the sub-basin of the Gloria fault at depths between 3500 and 4500m. Quantitative annotations of the observed fauna, as well as evidence of animal traces on the seafloor were explored in relation to topography, substrate type, and geochemical data acquired during surveys. Preliminary observations revealed a total of 121 morphospecies, of which Holothuroidea is the most diverse group, with 12 morphospecies. Deepest transects carried out along the main trace of Gloria Fault system showed the highest similarity among dives, predominantly characterised by soft sediment areas with Elpidiidae holothurians frequently observed. In contrast, the survey carried out at the Terceira ridge showed more diverse communities, which is likely due to a larger variability in substrate and topography. Specifically, soft-sediment sections showed a higher proportion of holothurians, ophiuroids and acorn worms, while unique Anthozoan and Porifera morphospecies were observed in areas with presence of hard substrates. The findings of this study provide unique knowledge of abyssal fauna associated with the Gloria Fault System, including areas inside of national jurisdiction and of relevance for management and conservation actions.